Penggunaan Strategi Pembelajaran Berbasis Guided-Critical Reading (GCR) Untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas IV SD Al-Hikmah Yapis - Parirak, Ressy Sabena; Basuki, Imam Agus; Rahayuningtyas, Wida (Universitas Nahdlatul Ulama Blitar, 2025)
Effective learning through a love of reading allows a person to absorb and interpret information from spoken and written sources. This research aims to improve the reading comprehension skills of fourth grade students at SD Al-Hikmah Yapis through the application of the guided-critical reading (GCR) strategy. This research is classroom action research (PTK) carried out in two cycles, with researchers acting directly from the beginning to the end of the action. PTK was chosen to increase teacher professionalism and improve teaching and learning activities in the classroom. The indicator of success in the student reading comprehension test is a minimum of 75% of students reaching the KKM (≥ 60). The results of the pre-test conducted on 20 students showed that only 5 students (25%) achieved the specified KKM, while 15 students (75%) had not yet completed it. However, after implementing the GCR strategy in the learning process, the results of the post-test cycle 1 showed a positive improvement. There are 50% of students who succeed in achieving scores above the KKM, so only 50% of students have scores below the KKM.